2019
DOI: 10.1073/pnas.1902483116
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the activity, aggregation, and toxicity of heterodimers of WT and ALS-associated mutant Sod1

Abstract: SignificanceAggregation of the antioxidant enzyme Sod1 represents common factors of both familial (fALS) and sporadic cases of ALS, a fatal neurodegenerative disease. Although many ALS studies have focused on Sod1 homodimers/homomers, the investigation of Sod1 heterodimers/heteromers remains controversial and has mostly been performed with recombinant proteins in vitro, in the absence of a cellular environment. By using living cells, this study sheds light into a critical issue in the context of fALS, the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…More than 185 SOD1 mutations have already been associated with ALS [ 13 ]. Although these mutations affect different locations within the SOD1 structure [ 16 ], many of them lead to protein-aggregation and increased oxidative damage, which are central events in ALS pathogenicity [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…More than 185 SOD1 mutations have already been associated with ALS [ 13 ]. Although these mutations affect different locations within the SOD1 structure [ 16 ], many of them lead to protein-aggregation and increased oxidative damage, which are central events in ALS pathogenicity [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant effect of SOD1 can also provide protection for cancer cells or other dysfunctional cells. Mutations of the SOD1 gene have been linked to numerous human diseases and cancers, such as and Down syndrome and familial amyotrophic lateral sclerosis (ALS), Indeed 20% of ALS cases are associated with mutations in SOD1 (Brasil et al, 2019), Somwar et al (2011) reported that SOD1 was overexpressed in lung adenocarcinomas when compared with the normal lung tissue, while Glasauer et al (2014) found that inhibition of SOD1 by the small molecule ATN-224 induced NSCLC cell death. SOD1 also acts as a metabolic focal point, integrating O 2 , nutrients, and reactive oxygen species (ROS) to direct energy metabolism (Tsang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantage of distinct electrophoretic mobilities of wild-type and mutant SOD1 proteins (G85R and L126Z), furthermore, wild-type human SOD1 was found to accumulate as detergent-insoluble aggregates with the mutant proteins in transgenic mice [ 29 , 31 , 33 , 34 ], while the interactions in the aggregates would not be simply a co-assembly of mutant and wild-type proteins [ 33 ]. A mechanism of disease-accelerating effects of wild-type SOD1 remains unclear, but heteromeric interactions between wild-type and mutant SOD1 appear to aggravate the aggregation and toxicity in cultured cell models [ 36 ] and have correlation with the disease severity [ 37 ]. It should be also noted that, in some studies, overexpression of wild-type human SOD1 did not affect the onset or duration of disease in mice expressing G85R-mutant human SOD1 [ 5 ] or G86R-mutant murine SOD1 [ 38 ].…”
Section: Introductionmentioning
confidence: 99%